2021
DOI: 10.3390/ijms22031425
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms and Treatment of Sarcopenia in Liver Disease: A Review of Current Knowledge

Abstract: Sarcopenia is characterized by progressive and generalized loss of skeletal muscle mass and strength that occurs with aging or in association with various diseases. The condition is prevalent worldwide and occurs more frequently in patients with chronic diseases owing to the intrinsic relationship of muscles with glucose, lipid, and protein metabolism. Liver cirrhosis is characterized by the progression of necro-inflammatory liver diseases, which leads to fibrosis, portal hypertension, and a catabolic state, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 94 publications
0
4
0
1
Order By: Relevance
“…The present study was not designed to elucidate the precise mechanisms involved in the effects of the multifactorial intervention. However, previous studies have reported that exercise improves muscle metabolism and quality, 44 that BCAA stimulates muscle protein synthesis by activating the mammalian target of the rapamycin (mTOR) pathway, 44 and that the multistrain probiotic can improve the proinflammatory state and hyperammonemia, 30 , 45 , 46 both factors favoring muscle wasting. 44 …”
Section: Discussionmentioning
confidence: 99%
“…The present study was not designed to elucidate the precise mechanisms involved in the effects of the multifactorial intervention. However, previous studies have reported that exercise improves muscle metabolism and quality, 44 that BCAA stimulates muscle protein synthesis by activating the mammalian target of the rapamycin (mTOR) pathway, 44 and that the multistrain probiotic can improve the proinflammatory state and hyperammonemia, 30 , 45 , 46 both factors favoring muscle wasting. 44 …”
Section: Discussionmentioning
confidence: 99%
“…In chronic liver disease, glycogen stores in the liver are depleted, and sugar is not available as an energy source, resulting in the breakdown of protein and lipids from muscle and adipose tissue and worsening nutritional status. In addition, the essential branched-chain amino acids (BCAAs) are involved in albumin synthesis and the maintenance of skeletal muscle mass, and thus, a decrease in BCAAs is also closely related to the development of sarcopenia in chronic liver disease [ 49 , 50 ]. Protein metabolism is assessed using serum albumin levels, the BCAA-to-tyrosine ratio (BTR), and albumin–bilirubin score [ 51 ], and their abnormal values are considered an indication for nutritional intervention for PEM.…”
Section: Alcohol-induced Metabolic Abnormalitiesmentioning
confidence: 99%
“…У больных с ЦП с сопутствующей саркопенией для лечения помимо физических упражнений и L-орнитин-L-аспартата (LOLA) применяются антибиотики, лактулоза, аминокислоты с разветвленной цепью, витамин D, цинк и диета [90]. Основная цель назначения антибиотиков больным с гипераммониемией и ПЭ заключается в подавлении уреазопродуцирующей кишечной микробиоты.…”
unclassified